MULTI-PURPOSE USE AND LIFECYCLE ANALYSIS OF SOLAR PANELS - Strušnik, Dušan; Novosel, Urška; Avsec, Jurij (Journal of Energy Technology, 2024)
The combined use of renewable energy technologies and alternative energy technologies is a promis-ing approach to reduce global warming effects throughout the world. In this paper, the solar panel is used in combination with a heat pump or with biomass sources to obtain heat, electricity, and hydrogen. Based on the Rankine thermodynamic cycle, hydrogen could be obtained from water with electrolysis and the CuCl thermochemical cycle. Furthermore, this study contains a life cycle analysis of solar panels.